The Kapuas District Attorney's Office in Palangkau's Legal Division's Communication Plan and Public Services - Saingan, Alalanda Ludus; Meitiana, Meitiana; Sintani, Lelo (Jurnal Ekonomi, 2025)
This research is entitled "Communication Strategy and Public Service in the Legal Area of Cabang Kejaksaan Negeri Kapuas in Palingkau". The purpose of this research is to find out and find steps in carrying out communication and public service activities in the jurisdiction of Cabjari Kapuas in Palingkau. This research uses a qualitative method. There were five informants, namely the Head of the Cabjari Kapuas in Palingkau, the Head of Development Affairs for the Cabjari Kapuas in Palingkau, Dadahup Sub-District Head, Palingkau Lama Sub-District Chief and Palingkau Baru Sub-District Head. Data collection techniques by conducting interviews and direct observation of the field as primary data and literature sources as secondary data. The data analysis technique consisted of 3 procedures: data reduction, data presentation and data verification. The study results concluded that communication still uses media belonging to external parties, and public services are still conventional. By involving external parties, agencies cannot avoid potentially harmful information. Traditional public services impact efficiency and effectiveness by using swot analysis found forming strategy websites to carry out communication and public service activities at the Cabang Kejaksaan Negeri Kapuas in Palingkau.